1998
DOI: 10.2165/00007256-199826050-00003
|View full text |Cite
|
Sign up to set email alerts
|

Applied Physiology of Water Polo

Abstract: Water polo has been played for over a century. While the rules of the game have evolved considerably over this time, the sport has consistently remained, physiologically, a highly demanding activity. Much attention has been paid to the technical and strategic elements of the game; however, despite the potential for improvements in athletic performance and the maintenance of athletes' health, there are few published studies (particularly in English) on the physical and physiological demands and adaptations to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
140
1
35

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(189 citation statements)
references
References 26 publications
13
140
1
35
Order By: Relevance
“…Water polo is a game which poses high physiological demands (26) on the players, due to the aquatic environment and the intermittent nature of the sport (14). The time-restricted offense results in repeated high-intensity swimming bouts (20).…”
Section: Introductionmentioning
confidence: 99%
“…Water polo is a game which poses high physiological demands (26) on the players, due to the aquatic environment and the intermittent nature of the sport (14). The time-restricted offense results in repeated high-intensity swimming bouts (20).…”
Section: Introductionmentioning
confidence: 99%
“…The mean value of stature for the Iranian was 184.0 cm while it was 187.4 for the Spanish. In the year 1998, Smith [26] described that national Greek team has mean height of 184.2 cm and also in 2004 Lozovina et al reported the statured of 189.5 cm for 65 water polo players from the top Croatian clubs [1]. So the valued who reported in other published showed that the stature value of Iranian team are in line with the national Greek team [26].…”
Section: Discussionmentioning
confidence: 91%
“…In the year 1998, Smith [26] described that national Greek team has mean height of 184.2 cm and also in 2004 Lozovina et al reported the statured of 189.5 cm for 65 water polo players from the top Croatian clubs [1]. So the valued who reported in other published showed that the stature value of Iranian team are in line with the national Greek team [26]. As all fitness experts know, taller height and a more or less heavy body is the most important factors for athlete's performance [20].…”
Section: Discussionmentioning
confidence: 99%
“…S314-S322, 2013. Water polo is a team sport and efforts of high intensity are made in less duration, where the players must swim, hyperextension, takes and send the ball with moments of rest or low intensity, where the players conduct battles against their opponents throughout contacts type (Smith, 1998;Wakayoshi, 1992). "Water polo consists of high intensity bursts of sprinting, interspersed with short periods of low to moderate intensity swimming".…”
Section: Introductionmentioning
confidence: 99%